(untitled) (Heritage, 2021)
Decision of the League of Communists of Yugoslavia to pay special attention to the development of the Autonomous Region of Kosovo and Metohija has radically changed the economic structure of the region. This was reflected in the opening of new plants in the electrical, chemical, textile and food industries, which was followed by the high rates of economic growth. These changes were made possible by investments from the federal and republican levels, which accounted for over 70% of total investments in Kosovo and Metohija. Data on the economic boom of Kosovo and Metohija in the period 1957–1964. years deny the myth of the "oppression of Albanians" while Aleksandar Rankovic was in positions of power. The increase in professional engagement and material investments at the end of the fifties enabled school buildings in Kosovo and Metohija to meet modern urban, hygienic and pedagogical standards. In order to improve interethnic relations, Serbian, Albanian and Turkish students from the same places started attending schools in the same facilities, and the Albanian language was introduced as an elective subject for Serbian students. During the 1950s, Kosovo Albanians rarely chose to study at Yugoslav universities, driven by cultural, economic and political considerations. The situation changed after 1958, with the establishment of the Higher Education School in Pristina. The faculty network expanded in the following years, so that in the early 1960s, Kosovo and Metohija had four towns that housed higher education institutions. Pristina has become the cultural, economic and educational center of this part of Yugoslavia.